Association between sleep and severe periodontitis in a nationally representative adult US population. Issue 6 (5th December 2019) - Alqaderi, Hend; Goodson, J. Max; Agaku, Israel
Abstract: Background: Poor sleep behavior appears to have adverse effects on health by metabolic disruption and immunity suppression. Sleep disturbance is strongly associated with diabetes, cardiovascular diseases, and some cancers. This study aimed to evaluate the association between sleep duration and periodontal disease in a national US population study in a National Health and Nutrition Examination Survey (NHANES). Methods: The data were collected from individuals aged ≥30 years and included 3, 624 participants in the United States NHANES 2013 to 2014. A weighted multivariable logistic regression modeling quantified the association between sleep and severe periodontal disease. We tested for diabetes as an effect modifier, adjusting for potential confounders such as smoking status, sex, age, education level, and dental visit. Results: Individuals who sleep >7 hours/night with no trouble sleeping are 40% less likely to have severe periodontal disease (odds ratio [OR] = 0.6, P < 0.05), adjusting for age, sex, smoking status, FPL, education level, and dental visit. Additionally, diabetes was a significant positive effect modifier of the relationship between sleep and severe periodontal disease (OR = 4.8, P < 0.05). Conclusions: Findings of this cross‐sectional representative study of an adult US population revealed a statistically significant association between sleep duration and severe periodontitis. In this study, individuals who slept >7 hours/night were less likely to exhibit severe periodontal disease. It also seems that this relationship was stronger among individuals with diabetes compared with individuals without diabetes.